ADVANCED MAGNETIC RESONANCE IMAGING (MRI) APPROACHES TO ASSESSING MILD TRAUMATIC BRAIN INJURY (MTBI) IN CHILDREN - Hasswa, Raghda (My University, 2015)
Despite the high incidence and potential cognitive, physical and emotional consequences of mild traumatic brain injury (mTBI), its pathophysiology and recovery time are not well understood. Furthermore, some mTBI patients’ post-concussion symptoms reappear with physical activity. In this project, three advanced MRI techniques (resting state functional magnetic resonance imaging (rs-fMRI), diffusion tensor imaging (DTI), and proton magnetic resonance spectroscopy (1H-MRS)) were used to investigate brain changes following mTBI in children and acute aerobic exercise in healthy adults. Children with mTBI were examined longitudinally at 1, 4 and 7 months post-injury. Functional connectivity of resting state networks (RSNs) was investigated using probabilistic independent component analysis. Statistical significance was discovered in three RSNs: decreased functional connectivity in the auditory network; and increased functional connectivity in the default mode network and sensorimotor network. There was some functional recovery observed at the second scan; however, a persistent increase in connectivity in the default mode network was observed. Furthermore, DTI whole-brain analysis was performed using tract-based spatial statistics. A statistically significant decrease in fractional anisotropy was found in the left inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, superior longitudinal fasciculus and forceps major. Moreover, 1H-MRS was acquired from the right frontal white matter (FWM) and anterior cingulate cortex. A statistically significant increase in glutamate in the FWM was found relative to controls. Our findings show that mTBI in children causes abnormalities in the brain’s RSNs, white matter tracts and neurometabolites, and these disruptions persist for at least 7 months following injury. The last part of this project involved the assessment of the effects of acute exercise on brain functional connectivity. It is well known that exercise can potentiate post-concussion symptoms. Thus, the goal of the last study was to assess the healthy brain changes, in preparation for examining patients following mTBI. Rs-fMRI was used to investigate the effects of acute aerobic exercise on the healthy brain. Statistical significance was discovered in three RSNs: increased functional connectivity in the executive control network and fronto-parietal network, and decreased functional connectivity in the sensorimotor network. Our findings provide evidence of changes in brain resting state functional connectivity following acute aerobic exercise. This may shed light on mTBI cases where post-concussion symptoms reappear with exercise.